The Differences of N–Acetyl–β–Glucosaminidase and β2 Microglobulin levels in Patients with and without Early Diabetic Nephropathy - Cynthia Citra; Edward Kurnia Setiawan Limijadi; Banundari Rachmawati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Diabetic Nephropathy (DN) is becoming the most serious microvascular complication, which be marked by the presence of persistent albuminuria. N–asetil–β–glucosaminidase is dominant lyzosom enzyme in the renal tubule epitel. β2 microglobulin is low molecular weight protein which produced by major histocompatibility complex class 1 (MHC-1) expressed cell in all nucleated cell. N–asetil–β–glucosaminidase and β2 microglobulin could be new usefull marker for early DN. Analytic observational study with cross sectional approach was conducted in May – July 2019 involving 27 non diabetic patients (K1), 27 diabetic patients without DN (K2) and 27 diabetic patients with early DN (K3) at the Clinical Pathology department of Faculty of Medicine, Diponegoro University and Diabetic Clinic. Data include age, gender, fasting blood glucose, blood preasure and urine albumin creatinine ratio. N–asetil–β–glucosaminidase level between groups were analyzed using Anova, β2 microglobulin level between groups using Kruskal Wallis, p<0.05 were considered significant. There are significant differences in levels of N–asetil–β–glucosaminidase between K1 and K2 (p =0.01), K1 and K3 (p =< 0.01), K2 and K3 (p = 0.03) and β2 microglobulin  between K1 and K2 (p = 0.02), K1 and K3 (p =< 0.01), K2 and K3 (p< 0.01). N-acetyl-β-glucosaminidase and β2 microglobulin levels were higher in K2 compared to K1 and increased higher in K3 compared to K1 and K2. N-acetyl-β-glucosaminidase and β2 microglobulin can be used as an alternative marker for early DN.